FENOMENA AL-TASYABBUH (PENYERUPAAN) DALAM SAMBUTAN PERAYAAN MASYARAKAT MAJMUK DI MALAYSIA - Ramli, Mohd Anuar; Ismail, Paizah; Abdullah, Ahmad Badri; Jamaludin, Mohammad Aizat (Jurnal Syariah, 2019)
This study discusses the issue of Muslim imitation of non-Muslims, particularly in respect of the celebrations of the multicultural society in Malaysia. Recently, arguments have emerged pertaining to the issue of Muslim practices of imitation of non-Muslim celebrations, such as participating in celebration in the temples or churches and wearing the special symbol of a particular religion. In accordance with this, the imitation phenomenon has raised jurisprudential implications for Muslims. This article attempts to analyse this kind of social phenomenon by referring to the traditions of the Prophet PBUH that strictly prohibited this practice. Moreover, this study discusses the patterns of imitation that are permitted and prohibited according to Islamic jurisprudence. The results of this study show there are prohibited imitations being practiced by Muslims in Malaysia, especially in respect of festivals and celebrations.